A New Map of the Province of Quebec according to the Royal Proclamation of the 7th of October 1763 from the French Surveys connected with those made after the War by Captain Carver, and Other Officers in His Majesty's Service - Carver, Jonathan, 1710-1780 (Creator)
Map of the Province of Quebec in 1776, after the French and Indian War. Cities, towns, bodies of water and other geographic features labelled throughout. Indigenous communities are noted, including the Nipissing First Nation and members of the Ottawa, Algonquin, and Abenaki peoples (sometimes noted by the names of regional subgroups). Relief shown pictorially. There are four inset maps in the upper left, including two of the Montreal area, Québec City, and the course of the St. Lawrence River. Scale is 1:2,250,000. Various scales at the bottom of the map are in British Miles, Nautic Leagues, and Canadian Leagues. Meridian is London. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .